Polemik Hukum Penunjukan Penjabat (PJ) Kepala Daerah Berdasarkan Undang Undang Nomor 10 Tahun 2016 Tentang Pemilihan Gubernur, Bupati dan Walikota - Yarni, Meri; Kosariza, Kosariza; Irwandi, Irwandi; Juanson, Juanson; Yanti, Herma; Taufani, A. Yuli (Wajah Hukum, 2023)
The appointment of acting regional heads to fill the vacancy for definitive regional head officials caused by postponing regional elections in 271 regions in Indonesia has created problems in the administration of government in Indonesia. Regarding Article 201 of Law No. 10 of 2016 concerning the Election of Governors, Regents and Mayors which is the legal basis for the appointment of acting regional heads, a judicial review has been carried out resulting in MKRI Decision Number 67/PUU-XIX/2021 and MKRI Decision Number 15/PUUXX /2022. These legal materials were obtained through literature study and analyzed descriptively-qualitatively. The postponement of the 2022 and 2023 regional elections is still causing polemics. Based on data from the Ministry of Home Affairs in May 2022, the needs for filling regional head officials include 5 provinces, 6 cities and 37 districts. Meanwhile, there are as many as 101 regional heads whose leadership terms will end in 2022 and as many as 170 regional heads and deputy heads in 2023. This means that 271 regional head positions will end before the 2024 simultaneous elections.